Cerita Rakyat sebagai Media Penanaman Karakter dalam Pembelajaran Bahasa Indonesia pada Siswa Kelas V SD: Folktales as a Medium for Character Building in Indonesian Language Learning for Fifth Grade Elementary School Students - Putri Ramadhani Mustari; Nurlaelah Mahmud; Suhartini Khalik; Suleha Suleha (Information Technology and Science(ITScience), 2026)
Character education in elementary schools is an important aspect in shaping students' attitudes and behavior. However, in practice, learning still tends to emphasize cognitive aspects rather than to strengthen character values in context. This condition indicates the need for integrating character values into the learning process, especially in Indonesian language learning. This study aims to describe the application of the local folktale Nene' Mallomo as a medium for character building in Indonesian language learning, and to analyze the characters that emerge among students based on Thomas Lickona's theory. This study uses a qualitative descriptive approach. The study's subjects were fifth-grade students at UPT SD Negeri 04 Benteng. Data collection techniques included observing the learning process, observing student character, conducting interviews, and documenting. The results showed that the folktale was applied across the opening, core, and closing learning stages, with strategies such as listening to and watching the story, character-value discussions, reflection, and case studies using sticky notes. The application includes three aspects of Lickona's character: moral knowing through question-and-answer activities and moral value analysis; moral feeling through student responses that show admiration for the character's firmness in upholding justice; and moral action through habituating students' moral attitudes and decision-making in the case study. Character traits evident in students include honesty, responsibility, fairness, respect for others, social awareness, and hard work. Therefore, local folklore can be used as a medium for Indonesian language learning to support character development in elementary schools.